2015
DOI: 10.1016/j.cellsig.2015.03.022
|View full text |Cite
|
Sign up to set email alerts
|

PKA and actin play critical roles as downstream effectors in MRP4-mediated regulation of fibroblast migration

Abstract: Multidrug resistance protein 4 (MRP4), a member of the ATP binding cassette transporter family, functions as a plasma membrane exporter of cyclic nucleotides. Recently, we demonstrated that fibroblasts lacking the Mrp4 gene migrate faster and contain higher cyclic-nucleotide levels. Here, we show that cAMP accumulation and protein kinase A (PKA) activity are higher and polarized in Mrp4−/− fibroblasts, versus Mrp4+/+ cells. MRP4-containing macromolecular complexes isolated from these fibroblasts contained seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…PKA activity can be monitored in real time using FRET-based sensor for PKA called pmAKAR3 7,17 . To check the specificity of pmAKAR3 for PKA activity, we treated HEK293 cells overexpressing pmAKAR3 or the point mutant pmAKAR3-TA, which contains a threonine-to-alanine mutation at substrate region for PKA and therefore irresponsive to PKA phosphorylation, with 25 μM of forskolin, a cAMP inducing agent 2 .…”
Section: Representative Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…PKA activity can be monitored in real time using FRET-based sensor for PKA called pmAKAR3 7,17 . To check the specificity of pmAKAR3 for PKA activity, we treated HEK293 cells overexpressing pmAKAR3 or the point mutant pmAKAR3-TA, which contains a threonine-to-alanine mutation at substrate region for PKA and therefore irresponsive to PKA phosphorylation, with 25 μM of forskolin, a cAMP inducing agent 2 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…IncuCyte ™ –based high content microscopy can capture and analyze cell behaviors like cell migration in a more convenient and accurate manner 18 . The high content microscopy data demonstrated that the effect of MRP4 on fibroblast migration is completely abolished by disruption of actin cytoskeleton or by inhibition of PKA 17 .…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…A number of the biological processes identified by GO analysis have been previously reported to be regulated by cAMP. These include mRNA splicing (64)(65)(66), spindle organization (67,68), fibroblast migration (69,70), lamellipodium assembly (71,72), apoptosis (73)(74)(75)(76), ATM signaling (77,78), gene silencing via microRNA (79)(80)(81)(82), T-cell selection (83), and cytoskeletal reorganization (84). This study suggests which molecular substrates might participate in the regulation of these processes.…”
Section: Biological Processes Regulated By Different Pde-regulatedmentioning
confidence: 99%